THE FAKTOR PENDORONG DAN PENARIK YANG MEMPENGARUHI MINAT WISATAWAN GENERASI-Z DALAM BERKUNJUNG KE DESTINASI WISATA LABUAN BAJO - Purba, Ishaktio Octavianto; Yustisia Pasfatima Mbulu; Azra Mashita (Fakultas Pariwisata Universitas Pancasila, 2024)
This research aims to identify push and pull factors and analyze the influence of push and pull factors on the interest of generation z tourists in visiting the Labuan Bajo tourist destination. The method used is descriptive quantitative. The independent variables of this research are escape, relaxing, play, strengthening family bonds, prestige, social interactions, romance, educational opportunity, self-fulfillment, and wish-fulfillment as well as pull factors, namely amenities, attraction, accessibility, and ancillary. Meanwhile, the dependent variable of this research is interest in visiting. The sample obtained was 110 respondents using purposive sampling technique. The hypothesis of this research was tested using IBM SPSS 27 with the results of the driving factor being the escape variable, namely getting away from routine, the relaxing variable, namely improving mental & physical health, the play variable, namely playing games, the strengthening family bonds variable, namely activities with the family, the prestige variable, namely increasing social status. , the social interaction variable, namely socializing with other people, the romance variable, namely enjoying a romantic atmosphere, the educational opportunity variable, namely gaining new knowledge, the self-fulfillment variable, namely challenging yourself, and finally the wish-fulfillment variable, namely realizing dreams and fantasies. Apart from that, the pull factor in the amenities variable is the overall positioning of infrastructure, the attraction variable is the attractiveness of natural beauty, the accessibility variable is the availability of supportive transportation, the ancillary variable is the existence of government support to support a destination worth visiting, and finally the visiting interest variable is interest. work or education. The results of the influence test state that the escape and play indicators partially have an influence on Generation Z's interest in visiting Labuan Bajo. Apart from that, other variables have no effect on Generation Z's interest in visiting Labuan Bajo.